Komunikasi Profetik Dalam Media Sosial Komunitas Musisi Mengaji Bandung - Sari, Ratu Arti Wulan (Media Nusantara, 2022)
Musisi Mengaji Community (Komuji) Bandung is a community that is unique because it is formed from two similarities, namely the love of music and the need to study religion. Their community activities are reflected in Komuji’s Instagram social media @komuji_indonesia which already has 22.7 thousand followers. This study aims to determine how prophetic communication is used in the Instagram social media of Musisi Mengaji Community (Komuji) as a community that carries religious values as well as the art of music. The method used in this research is descriptive qualitative method using the Theory of Prophetic Social Sciences which was initiated by Kuntowijoyo. The data collection techniques used 3 (three) ways, namely observation, interviews, and literature study. The results show that there are prophetic values in the @komuji_indonesia Instagram account, namely (1) Humanization, Instagram @komuji_indonesia represents the pillars of Humanization in its various collaboration events, namely containing the same human dignity even though they have differences in various things, caring for togetherness, and upholding tolerance between humans. (2) Liberation (liberation), Instagram @komuji_indonesia in its content has the pillar of Liberation in an effort to liberate the knowledge system and the economic system through its content. And (3) Transcendence, in the content on the @komuji_indonesia Instagram account, it represents this pillar where everything, both words and actions, is centered on God Almighty